Literature review on knowledge transfer models: From Shannon- Weaver (1949) to Kostova (1999) - ELHMAIDI Khadija; TIJANI Omar (African Scientific Journal, 2023)
The mechanisms of knowledge transfer have always interested many researchers. Since it is an important element in the understanding of knowledge management. Based on the evolution of research work, this article reviews five typical models of knowledge transfer from Schannon-Weaver (1949), Szulanski (1996), Nonaka and Takeuchi (1995), Boisot (1995), and Kostova (1999). The purpose of this article is to analyze the relationship between these models of knowledge transfer, and concludes that the relationship is not a line but a network. The focus of future research is to make the models uniform and to conduct more empirical research.